Tracking the complete degradation lifecycle of poly(ethyl cyanoacrylate): From induced photoluminescence to nitrogen-doped nano-graphene precursor residue. (January 2022) - Fontecha, Daniela; Mahn, Chelsea; Bochinski, Jason R.; Clarke, Laura I.
Highlights: Superglue (a polymer called poly(ethyl cyanoacrylate)) degrades at moderate temperatures by reverting to a volatile monomer, but also has a side-reaction that forms a carbonaceous by-product. During thermal degradation, superglue also forms a luminescent by-product. The photoluminescence observed from heated superglue is depolarized and shifts toward lower energy emission as the thermal degradation progresses. The final end product of superglue degrading by heating is a non-luminescent graphene-like residue. Abstract: Poly(ethyl cyanoacrylate) (PECA) is a commercial polymer which degrades easily at temperatures between 150 - 200 °C via an unzipping reaction where volatile monomer is produced. In this report, the complete moderate-temperature degradation lifecycle is delineated, which also includes formation of a carbonaceous by-product where the ester side groups are lost and ring formation between the backbone and cyano side group occurs. Degradation-induced photoluminescence is observed at an intermediate point where the remaining PECA (or re-polymerized oligomers) has sp 3 carbons but sp 2 -carbon-containing clusters of the by-product that will ultimately form aromatic structures are also present. This observation supports the hypothesis that degradation-induced photoluminescence in polymers, which has been observed widely, is connected to the formation of such sp 2 containing clusters, and that this process is relatively independent of the original polymer chemistry, as PECA dominantly degrades through a mechanism distinctly different than the thermo-oxidative cascade associated with many thermoplastic materials. As degradation further advances, a residue of approximately 8% of the original mass is produced which is no longer photoluminescent and can ultimately transform into nitrogen-substituted nano-graphene. Observing the entire lifecycle further solidifies the previously-proposed connection between degradation-induced luminescence in polymers and photoluminescence in hydrogenated amorphous carbon. The low degradation temperature of PECA also provides a bridge between classic polymer degradation and waste-to-graphene strategies that generally involve much more aggressive processing.